2013
DOI: 10.1063/1.4818001
|View full text |Cite
|
Sign up to set email alerts
|

Surfaces of colloidal PbSe nanocrystals probed by thin-film positron annihilation spectroscopy

Abstract: Positron annihilation lifetime spectroscopy and positron-electron momentum density (PEMD) studies on multilayers of PbSe nanocrystals (NCs), supported by transmission electron microscopy, show that positrons are strongly trapped at NC surfaces, where they provide insight into the surface composition and electronic structure of PbSe NCs. Our analysis indicates abundant annihilation of positrons with Se electrons at the NC surfaces and with O electrons of the oleic ligands bound to Pb ad-atoms at the NC surfaces… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…[2][3][4][5][6][7] The Tam et al explained important advanced characterization used for defects in ZnO nanorods based on positron annihilation spectroscopy (PAS). 8 By using slow positron beams the PAS can also uniquely probe the outermost surfaces of nano-structured semiconductor materials as recently demonstrated by Chai et al 9 In addition, magnetic properties can be modified by introducing 3d-transition metal impurities into the ZnO lattice. A few studies have suggested that transition metal doped ZnO nanostructures possess interesting magnetic properties along with optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The Tam et al explained important advanced characterization used for defects in ZnO nanorods based on positron annihilation spectroscopy (PAS). 8 By using slow positron beams the PAS can also uniquely probe the outermost surfaces of nano-structured semiconductor materials as recently demonstrated by Chai et al 9 In addition, magnetic properties can be modified by introducing 3d-transition metal impurities into the ZnO lattice. A few studies have suggested that transition metal doped ZnO nanostructures possess interesting magnetic properties along with optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous positron lifetime experiments have shown that more than 90% of positrons implanted in a layer of PbSe QDs capped with Oleic Acid (OA) ligands trap at the surface of PbSe QDs, 16 where the positron is bound in a potential well behaving like a image potential at large distances (Figure 1). 20,21 Positrons implanted in the PbSe QD layer primarily lose their high initial kinetic energy in the PbSe cores of the QDs where they thermalize.…”
Section: Introductionmentioning
confidence: 99%
“…caused mostly by quantum confinement of the Se(4p) valence electron orbitals, 16 positron confinement 28,29 and other small contributions of atoms at the surface connected with the ligands. 16 The confinement of valence electrons and positrons for PbSe QDs capped with OA and OLA ligands leads to a small difference in the 1 a.u. peak area, 16,30 since the QDs have comparable sizes and the ligands have the same large chain length.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations